Correlation among mandibular, femoral, lumbar and cervical bone density - Scheibel, Paula Cabrini; Matheus, Paula Daniele; Albino, Cláudio Cordeiro; Ramos, Adilson Luiz [UNESP] (FapUNIFESP (SciELO), 2009)
Introduction: Due to the rise in frequency of adult patients who currently are submitted to orthodontic treatment, general health conditions of this age have been a reason of inquiries correlated to events related to bone metabolism, as dental movements are dependent on the process of bone remodeling, even though in a local level. Different standards of bone density can give different answers to the orthodontic movement. Aim: The present study evaluated the correlation of the general bone mineral density (BMD) to the mandibular region. Methods: Therefore, 22 healthy women aged between 30 and 45 years old were selected for bone densitometry examinations of lumbar, cervical, femoral, as well as mandibular alveolar region. The correlations to these readings were tested as well as values of reference were established for cervical and mandibular areas. Results: The results did not demonstrate significant correlation among the mandibular density to the others studied areas. There was only significant correlation between cervical and femural region. Normal BMD average value for mandibular region was 0.983g/cm2 (SD=0.334), whereas for cervical region was 0.768g/cm2 (SD=0.102), and the average values for lumbar and femoral regions were respectively 1.127g/cm2 (SD=0.067) and 0.925g/cm2 (SD=0.078), these last ones were similar to the reference values of World Health Organization (WHO). Conclusions: It is suggested that the examination of the femoral area can comprehend the expected value to cervical area, however particular densitometry examination for the mandibular area is needed, and the exploration of the traditional values (lumbar and femoral) is not appropriate to the estimative of this area. Additional studies are necessary to evaluate local density variations and its influence on orthodontic movement.
Correlação entre a densidade óssea mandibular, femural, lombar e cervical
Keywords: Bone densitometry; Bone remodeling; Mandibular bone density; Orthodontic movement; Osteoporosis